2013
DOI: 10.1371/journal.pmed.1001444
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of Mycoplasma pneumoniae in the Upper Respiratory Tract of Symptomatic and Asymptomatic Children: An Observational Study

Abstract: In order to determine the possible asymptomatic carriage of Mycoplasma pneumoniae in the upper respiratory tracts of children, Emiel Spuesens and colleagues investigate the prevalence of M. pneumoniae in symptomatic and asymptomatic children at a hospital in The Netherlands. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
222
5
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(250 citation statements)
references
References 26 publications
6
222
5
13
Order By: Relevance
“…However, the diagnostics of bacterial infections in children with respiratory infections are difficult because blood culture results are rarely positive, sputum or samples from bronchoalveolar lavage are difficult to obtain, 37 and the clinical significance of bacterial diagnostics from the nasopharynx in children with ARI is limited due to high rates of colonization of common bacterial pathogens. 38,39 Finally, the qPCR method used in our study was not appropriate to adequately assess viral load, which has been found to be associated with severity of disease. 40 …”
Section: Discussionmentioning
confidence: 87%
“…However, the diagnostics of bacterial infections in children with respiratory infections are difficult because blood culture results are rarely positive, sputum or samples from bronchoalveolar lavage are difficult to obtain, 37 and the clinical significance of bacterial diagnostics from the nasopharynx in children with ARI is limited due to high rates of colonization of common bacterial pathogens. 38,39 Finally, the qPCR method used in our study was not appropriate to adequately assess viral load, which has been found to be associated with severity of disease. 40 …”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, cultural and molecular detection of M. pneumoniae in healthy individuals and long-term carriage of bacteria after the period of typical respiratory symptoms and adequate antibiotic therapy are known facts (18,19). Future studies have to prove whether a range of bacterial load is associated with this phenomenon and might be used to differentiate patients with acute illness due to M. pneumoniae from symptom-less carriers or M. pneumoniae-positive patients with symptoms of CAP caused by other microorganisms (20). In this context, knowledge of the sensitivity of the real-time PCR approach used is a precondition for the evaluation of the significance of the concentration of genome copies measured.…”
mentioning
confidence: 99%
“…[3,9,12] Recent studies have also shown that asymptomatic carriage of Mp in the upper respiratory tract is common in children. [5,13] EEG is often abnormal with diffuse slowing, as in our patient; focal abnormalities are less common. [3,12] Brain MRI shows abnormalities in about half of the patients, mainly focal ischaemia or edema, or increased signal intensities.…”
Section: Discussionmentioning
confidence: 47%